Comparing higher education systems in selected Asia Pacific countries: implications for Malaysia - Kaur, Sarjit; Abdul Rahman, Shukran; Koo, Yew Liw; Zakariya, Hafiz; Mohammad Lotfie, Maskanah (Institut Penyelidikan Pendidikan Tinggi Negara (IPPTN), 2013)
With the continuing emphasis placed on higher education institutions in many countries to produce knowledge workers for the next generation, there has been a continuous demand to strengthen the provision and delivery of higher education systems. This has resulted in an extraordinary expansion and intensification of internet use - “between the end of 2000 and 2008, worldwide internet users increased from 361 million to 1,581 million”